Representasi Feminisme dalam Cerpen “Perempuan Itu Pernah Cantik” Karya Mashdar Zainal - Pradicta Nurhuda (Indonesian Journal of Applied Linguistics Review, 2022)
The issue of feminism can be seen from several stories in literary works, one of which is short stories. This research was conducted with the aim of looking at the forms of injustice experienced by women based on marginalization, subordination, stereotypes, workload, and violence experienced by the main character in the short story "Perempuan Itu Pernah Cantik" by Mashdar Zainal. The research method used is descriptive qualitative method. The results of the study show that (1) female characters experience marginalization as a wife before the wife must submit to her husband regardless of the conditions experienced in her family; (2) female characters experience subordination in their families in the form of a lower position than their husbands so that the husband has the right to order his wife; (3) female characters experience stereotypes in the form of a wife having to serve her husband as well as possible even though she is already tired of doing a lot of housework; (4) female figures get a very tiring workload every day because all housework is done by the wife herself, while the husband never helps with household chores because of busy work; and (5) the main character does not experience physical violence, but experiences tremendous psychological stress because she used to be a beautiful model now just a housewife who never finishes with housework.